2020
DOI: 10.7717/peerj.8950
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome for the breast muscle of Jinghai yellow chicken at early growth stages

Abstract: Background. The meat quality of yellow feathered broilers is better than the quality of its production. Growth traits are important in the broiler industry. The exploration of regulation mechanisms for the skeletal muscle would help to increase the growth performance of chickens. At present, some progress has been made by researchers, but the molecular mechanisms of the skeletal muscle still remain unclear and need to be improved. Methods. In this study, the breast muscles of fast-and slow-growing female Jingh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Transcriptome sequencing of 16-week-old Bian chickens with varying growth rates revealed 108 differential genes; 17 were up-regulated, whereas 91 were down-regulated [19]. Moreover, 364, 219, and 111 differentially expressed genes (F8FvsF4F, F8SvsF4S, and M8SvsM4S) were detected for the three comparison groups, respectively, which used the 4-week old and 8-week old males and female of Jinghai yellow chicken with different growth rates [13]. In the later stage of embryonic development, the number of differentially expressed genes decreased sharply.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transcriptome sequencing of 16-week-old Bian chickens with varying growth rates revealed 108 differential genes; 17 were up-regulated, whereas 91 were down-regulated [19]. Moreover, 364, 219, and 111 differentially expressed genes (F8FvsF4F, F8SvsF4S, and M8SvsM4S) were detected for the three comparison groups, respectively, which used the 4-week old and 8-week old males and female of Jinghai yellow chicken with different growth rates [13]. In the later stage of embryonic development, the number of differentially expressed genes decreased sharply.…”
Section: Discussionmentioning
confidence: 98%
“…RNA-seq technology proved helpful in revealing the essential genes and pathways associated with muscle development. In previous experiments, different growth rate chicken (Jinghai Yellow Chicken) muscle was used to analyze the expression difference of genes about muscle development, which revealed the regulation mechanism of the growth chickens [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang ZR et al also found that the ECM-receptor interaction, MAPK signaling pathway, and focal adhesion, were the most enriched DEGs in breast muscle of chickens [ 15 ]. Zhao YQ et al found that focal adhesion, protein digestion and absorption, GABAergic synapse, axon guidance, ECM-receptor interaction, MAPK signaling pathway, arginine, and proline metabolism were closely related to skeletal muscle of Tongcheng pigs, while oxidative phosphorylation, Huntington’s disease, ribosome biogenesis in eukaryotes, metabolic pathways, Alzheimer’s disease, glycolysis/gluconeogenesis, and proteasome were found to be more associated with the DEGs in skeletal muscle of Yorkshire pigs at developmental stages [ 73 ]. The biological processes categories in this study, including “negative regulation of skeletal muscle tissue development”, “embryonic skeletal system morphogenesis”, and “regulation of skeletal muscle contraction”, were significantly regulated by the DEGs, indicating that these DEGs played a key role in regulating duck skeletal muscle development at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq technology proved helpful in revealing the essential genes and pathways associated with muscle development. In previous studys, different growth rate chicken (Jinghai Yellow Chicken) muscle was used to analyze the expression difference of genes about muscle development, which revealed the regulation mechanism of the differently growth chickens [ 11 , 12 ]. Transcriptome sequencing was performed on the breast muscle and leg muscle of Hanzhong Mabu ducks at several time points during embryo and postnatal period to find the key genes that play regulatory roles at different time points, and to provide a basis for further research on the growth and development mechanism of duck skeletal muscle[ 13 ].Zhao et al[ 14 ] used longissimus dorsi muscle of Lantang and Landrace pig at different gestation times as the research object to explore the muscle development rules of pig embryos of different breeds.…”
Section: Introductionmentioning
confidence: 99%